Learning Innovation in Islamic Boarding Schools in Improving the Quality of Islamic Education and Student Skills - Ahmad Qusairi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the implementation of learning innovations in Islamic boarding schools (pesantren) in East Java and their impact on the quality of Islamic education and student skills. Utilizing a qualitative approach, the research involved interviews, observations, and documentation from four pesantren, gathering insights from 20 informants, including foundation leaders, curriculum representatives, teachers, and students. The findings revealed diverse opinions on the need for innovation, highlighting strong support from leadership while underscoring challenges faced by teachers, particularly related to training and resource availability. The participation of students in the learning process emerged as a crucial element, emphasizing their interest in more interactive methods but also their desire for improved teaching quality. Supporting factors, such as parental involvement, were identified as beneficial, while hindering factors included insufficient ongoing teacher training and a lack of modern technological resources. Additionally, the study showed varied academic results among students, with approximately 70% of those involved in innovative learning achieving above-average scores, contrasting with 50% from traditional methods. The research concludes that a collaborative approach involving all stakeholders—teachers, students, parents, and pesantren administrators—is essential for the sustained development of educational innovations and improving academic outcomes. By addressing the identified challenges and leveraging the supporting factors, pesantren can create a more effective and innovative learning environment that meets the evolving needs of students. Islamic boarding schools, learning innovations, quality of education, teacher training, parental involvement, academic performance.